PENGARUH MODUL TERINTEGRASI AUGMENTED REALITY PADA MATERI KEANEKARAGAMAN HAYATI TERHADAP PEMAHAMAN KONSEP SISWA KELAS IV SDN KOTA BENGKULU - Wita Riska, Amanda; Noperman, Feri; Kurniawati, Ike (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of an Augmented Reality (AR)-integrated module on fourth-grade students' conceptual understanding of biodiversity. The study employed a quasi-experimental method using the matching-only pretest-posttest control group design. The research sample consisted of 26 fourth-grade students from SDN 06 Kota Bengkulu as the experimental group and 29 fourth-grade students from SDN 37 Kota Bengkulu as the control group. Data were collected through multiple-choice tests administered during the pretest and posttest. The data were analyzed using normality, homogeneity, and independent samples t-tests. The results showed that the mean posttest score of the experimental group (78.21) was higher than that of the control group (66.29). The independent samples t-test yielded a significance value of 0.022 (< 0.05), indicating a significant effect of the AR-integrated module on students' conceptual understanding. This result was attributed to the different learning treatments implemented in each group. The experimental group received instruction using the AR-integrated module, whereas the control group did not use the module during the learning process. The findings revealed a significant difference in the mean scores between the two groups. Therefore, it can be concluded that the AR-integrated module had a significant effect on improving fourth-grade students' conceptual understanding of biodiversity.